EFEKTIVITAS PEMBAYARAN PAJAK KENDARAAN BERMOTOR MELALUI APLIKASI E-SAMSAT PADA UNIT PELAYANAN PENDAPATAN DAERAH SAMSAT BANJARMASIN 1 - Mailiana, Mailiana; Hayati, Diana; Budiati, Penta Lestarini (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2024)
Abstract, The aims of this research are (1) to determine the effectiveness of motor vehicle tax payment services via the E-Samsat application and (2) determine the comparison between users of conventional motor vehicle tax payment services and those using the application E-Samsat at the Banjarmasin Samsat Regional Revenue Service Unit Office. The research method used in this research is descriptive research. The population in this study were people in the motor vehicle tax payment service at the Banjarmasin Samsat Regional Revenue Service Unit Office 1. The sample in this study was 124 respondents. The data sources in this research are primary data and secondary data. The research results show that (1) effectiveness related to procedures and services, E-Samsat can make it easier for people who are far from the city to minimize delays, because it can be done anytime and anywhere, and (2) this e-Samsat application, customers feel the ease of the application.